Spondylodiskitis and endocarditis due to Streptococcus gordonii - Ziv Dadon; Assaf Cohen; Yael M. Szterenlicht; Marc V. Assous; Yair Barzilay; David Raveh-Brawer; Amos M. Yinnon; Gabriel Munter (BMC, 2017)
Abstract Background Streptococcus gordonii is an infrequent cause of infective endocarditis (IE); associated spondylodiskitis has not yet been described in the literature. Purpose We describe 2 patients who presented with new-onset, severe back pain; blood cultures revealed S. gordonii bacteremia, which led to the diagnosis of spondylodiskitis and IE. We review our 2-decade experience with S. gordonii bacteremia to describe the clinical and epidemiological characteristics of these patients. Results In our hospital over the last 20 years (1998-2017), a total of 15 patients with S. gordonii bacteremia were diagnosed, including 11 men and 4 women, and the mean age was 65 ± 22 (range 23-95). The most common diagnosis was IE (9 patients), spondylodiskitis (the presented 2 patients, who in addition were diagnosed with endocarditis), necrotizing fasciitis (1), sternitis (1), septic arthritis (1) and pneumonia (1). The 11 patients with IE were treated with penicillin ± gentamicin, or ceftriaxone for 6 weeks, 5 required valve surgery and 10/11 (91%) attained complete cure. The 2 patients with diskitis required 2-3 months of intravenous antibiotics to achieve complete cure. Conclusion Spondylodiskitis was the presenting symptom of 2/11 (18%) patients with S. gordonii endocarditis. Spondylodiskitis should probably be looked for in patients diagnosed with S. gordonii endocarditis and back pain as duration of antibiotic treatment to achieve complete cure may be considerably longer.